Granzyme B‐expressing neutrophils correlate with bacterial load in granulomas from Mycobacterium tuberculosis‐infected cynomolgus macaques. (12th March 2015) - Mattila, Joshua T.; Maiello, Pauline; Sun, Tao; Via, Laura E.; Flynn, JoAnne L.
Summary: The role of neutrophils in tuberculosis (TB), and whether neutrophils express granzyme B (grzB), a pro‐apoptotic enzyme associated with cytotoxic T cells, is controversial. We examined neutrophils in peripheral blood (PB) and lung granulomas of M ycobacterium tuberculosis ‐infected cynomolgus macaques and humans to determine whether mycobacterial products or pro‐inflammatory factors induce neutrophil grzB expression. We found large numbers of grzB‐expressing neutrophils in macaque and human granulomas and these cells contained more grzB+ granules than T cells. Higher neutrophil, but not T cell, grzB expression correlated with increased bacterial load. Although unstimulated PB neutrophils lacked grzB expression, grzB expression increased upon exposure to M . tuberculosis bacilli, M . tuberculosis culture filtrate protein or lipopolysaccharide from E scherichia coli . Perforin is required for granzyme‐mediated cytotoxicity by T cells, but was not observed in PB or granuloma neutrophils. Nonetheless, stimulated PB neutrophils secreted grzB as determined by enzyme‐linked immunospot assays. Purified grzB was not bactericidal or bacteriostatic, suggesting secreted neutrophil grzB acts on extracellular targets, potentially enhancing neutrophil migration through extracellular matrix and regulating apoptosis or activation in other cell types. These data indicate mycobacterial products and the pro‐inflammatory environment of granulomas up‐regulates neutrophil grzB expression and suggests a previously unappreciated aspect of neutrophil biology in TB. Abstract : Large numbers of neutrophils in tuberculous granulomas are correlated with poor outcomes, but the mechanisms underlying this relationship are not understood. We found that neutrophils in macaque and human granulomas express granzyme B, a serine protease associated with cytotoxic lymphocytes, and that macaque neutrophils secreted granzyme B in response to stimulation by mycobacterial ligands. Numbers of granzyme B+granules per neutrophil correlated with bacterial burden per granuloma, suggesting neutrophil granzyme B may be an unexplored factor promoting pathology in tuberculosis.